The Dynamics of Women’s Leadership Based on Islamic Values: A Sociological Analysis of Educational Institutions at the SMP IT Boarding School and SMP Al Islam Mujahidin in Cilacap - Agus Suwanto; Muh. Hanif (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines the institutional context surrounding Islamic values-based women’s leadership in two private Islamic junior high schools in Cilacap, Central Java, Indonesia. Using a qualitative comparative documentary case study with a sociological orientation, the research analyzes scholarly publications, official educational records, accreditation data, institutional profiles, and publicly accessible materials. Data were organized through a document-review matrix and examined using thematic coding, within-case analysis, cross-case comparison, and sociological interpretation. The analysis focused on four interconnected themes: institutional legitimacy and Islamic school identity; discipline, character development, and religious culture; community communication and social capital; and gender-responsive leadership conditions. The findings indicate that the institutional space surrounding women’s leadership is shaped not only by individual capacity but also by the interaction of Islamic values, organizational arrangements, religious practices, and relationships of trust among schools, foundations, parents, and communities. The two cases share a common Islamic educational orientation but demonstrate different institutional configurations, suggesting that similar religious identities do not necessarily generate identical conditions for leadership legitimacy and authority. The study contributes a sociological perspective that connects women’s leadership in Islamic education with institutional legitimacy, religious culture, and social capital. Practically, it highlights the importance of inclusive organizational support, transparent communication, and collaborative institutional relationships. Because the study relies on documentary evidence, future field-based research is needed to examine how these conditions are experienced and negotiated in everyday leadership practice.